Pelatihan Pembuatan Minyak Telon pada Siswa SMKS Farmasi Putra Bangsa - Mita, maria_mita_susanti (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2024)
Telon oil is a blend of fennel oil (Oleum Foeniculi), Eucalyptus oil (Oleum Cajuputi) and coconut oil (Oleum Cocos) in certain proportions. The composition of each oil in telon oil is usually 1:1:3. Coconut oil functions as a carrier or solvent. Telon oil is useful for preventing and treating flatulence and providing a warm feeling. Apart from that, telon oil can relieve symptoms of colic and heartburn. Telon oil can be produced and developed personally. Information on making telon oil can be conveyed through outreach activities. Starting from this background, the community service team will hold a training in making telon oil which will be attended by class XII students with the aim of providing an applicative introduction that can be used as a development in the health sector. The service activities were carried out for 1 day on January 16 2024. From the results of the community service activities, it can be seen that the students were enthusiastic and enthusiastic in participating in the activities from start to finish, the students were able to apply the results of the counseling and training on making telon oil for health care at home. each. This training can be used to improve skills for Putra Bangsa Pharmacy Vocational School students. The results of the training showed that students were able to understand the function and formula for making telon oil.